2014
DOI: 10.1007/s00586-014-3435-3
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to corpus callosum anomalies in idiopathic scoliosis using diffusion tensor magnetic resonance imaging

Abstract: Purpose Idiopathic scoliosis (IS) is a frequent 3D structural deformity of the spine with a multi-factorial aetiology which remains largely unclear. In the last decade, human magnetic resonance imaging (MRI) morphometry studies (e.g. cortical thickness, 2D shape of the corpus callosum) have aimed to investigate the potential contribution of the central nervous system in the etiopathogenesis of IS. Recent developments in diffusion tensor imaging (DTI) allow us to extend the previous work to the study of white m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In AIS, some authors have concentrated on muscle and peripheral nerve disturbances, but in other studies impairment of the spinal cord and different pattern of brain activation has been published [7][8][9]. These observations demonstrate that central nervous system involvement with abnormal sensorimotor integration may underlie the pathogenesis of idiopathic scoliosis [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…In AIS, some authors have concentrated on muscle and peripheral nerve disturbances, but in other studies impairment of the spinal cord and different pattern of brain activation has been published [7][8][9]. These observations demonstrate that central nervous system involvement with abnormal sensorimotor integration may underlie the pathogenesis of idiopathic scoliosis [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…5,39 Therefore, our results suggest that the patients' brains have decreased myelination and fiber orientation in the body of the CC. These overall differences in DTI characteristics between healthy subjects and our patient population provide evidence that the CC is impacted by distal neuropathologies, [25][26][27][28][29][30] potentially due to Wallerian Degeneration caused by the tumors. 30,31 However, between each patient group, the differences in DTI characteristics suggest an altered response in the patients' brains that is determined by the type of the tumor.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, our results suggest that the patients’ brains have decreased myelination and fiber orientation in the body of the CC. These overall differences in DTI characteristics between healthy subjects and our patient population provide evidence that the CC is impacted by distal neuropathologies, potentially due to Wallerian Degeneration caused by the tumors …”
Section: Discussionmentioning
confidence: 80%
“…A previous DTI study of the spinal cord and hindbrain showed lower FA values in the medulla oblongata and cervical spinal cord. 4 Another DTI study by Joly et al 15 found a significant decrease in FA values in the midbody of the CC, which possibly suggests abnormal brain development in AIS.…”
Section: Abbreviationsmentioning
confidence: 97%
“…We also conducted the left-right comparison, which was not performed in the previous 2D study. 15 FA values were compared between the left and right sides of the CC, summarized in Fig 5 and Table 3. Lower FA values were found significantly on the left side of splenium (corrected P ϭ .012) and in the left genu (corrected P ϭ .03).…”
Section: D Roi Analysis Of the Corpus Callosummentioning
confidence: 99%